2016
DOI: 10.1186/s12885-016-2689-z
|View full text |Cite
|
Sign up to set email alerts
|

Environmental, maternal, and reproductive risk factors for childhood acute lymphoblastic leukemia in Egypt: a case-control study

Abstract: BackgroundAcute lymphocytic leukemia (ALL) is the most common pediatric cancer. The exact cause is not known in most cases, but past epidemiological research has suggested a number of potential risk factors. This study evaluated associations between environmental and parental factors and the risk for ALL in Egyptian children to gain insight into risk factors in this developing country. Methods: We conducted a case-control design from May 2009 to February 2012. Cases were recruited from Children’s Cancer Hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 47 publications
2
15
2
2
Order By: Relevance
“…(14,15) Parental smoking or passive smoke exposure of mother or child also posed a potential risk for child leukemia. (16,17) Growing evidence revealed positive associations between childhood leukemia and childhood exposure to household or agriculture pesticides. (18)(19)(20)(21) Published Egyptian studies on risk factors of childhood leukemia are limited, (16) and no previous study explored these risk factors in Upper Egyptian children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(14,15) Parental smoking or passive smoke exposure of mother or child also posed a potential risk for child leukemia. (16,17) Growing evidence revealed positive associations between childhood leukemia and childhood exposure to household or agriculture pesticides. (18)(19)(20)(21) Published Egyptian studies on risk factors of childhood leukemia are limited, (16) and no previous study explored these risk factors in Upper Egyptian children.…”
Section: Introductionmentioning
confidence: 99%
“…(16,17) Growing evidence revealed positive associations between childhood leukemia and childhood exposure to household or agriculture pesticides. (18)(19)(20)(21) Published Egyptian studies on risk factors of childhood leukemia are limited, (16) and no previous study explored these risk factors in Upper Egyptian children. This study aimed to identify potential child, parental, and environmental factors that contribute to leukemia risk among Egyptian children in Assiut Governorate.…”
Section: Introductionmentioning
confidence: 99%
“…However, outcome of individual studies in this review showed that in distribution of GSTM1 genotype, three had increase risk of association with null genotype [19,27,44] and two had no significant difference in prevalence of null genotype [22,24] whiles one study with a gender stratified analysis showed that the null genotype was over-represented in boys [21]. In environmental exposures of chemical pesticides and tobacco smoke 83.3% shows increase risk of childhood ALL [20,23,[27][28][29][30][31][32][33]] and 16.7% shows no association with childhood acute lymphoblastic leukemia [34,35].…”
Section: Discussionmentioning
confidence: 76%
“…Childhood acute lymphoblastic leukemia (ALL) comprises about 30% of malignancies in childhood [1], and constitutes 80% of childhood leukemias [2]. In Egypt, the annual incidence of childhood ALL is about 4 cases per 100,000 children and accounts for approximately 20% of pediatric malignancies [3].…”
Section: Introductionmentioning
confidence: 99%